(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Because there are more used car tyres produced each year, disposing of them has become a significant environmental issue on a global scale. Utilizing used tyres will reduce the effect on the environment and increase resource preservation. The stabilisation of soils using CRP (5%, 10%, 15%) is discussed in this article. The conduct and effectiveness of the stabilised soil were evaluated using the soil properties, compaction, California bearing ratio (CBR), and direct shear test. When soil and CRP are combined, it is seen that the maximum dry density and ideal moisture content decline as the percentage of crumb rubber in the soil increases. Bearing capacity and tensile strength are barely affected by blending. Nevertheless, the numbers stayed within reasonable bounds.